The Effect of an Escape Room in Psychiatric Nursing Education on Knowledge, Proactivity in Problem-solving, Teamwork, and Learning Satisfaction of Nursing students: A Quasi-experimental Study. - Hahn, Sukwon; Ryu, Young Mi (Journal of Korean Academy of Psychiatric & Mental Health Nursing (JKPMHN), 2024)
Purpose: This study assessed the effects of a psychiatric nursing class applying an escape room activity on nursing students' knowledge, proactivity in problem-solving, teamwork, and learning satisfaction. Methods: A non-equivalent control group design with pretest-posttest measures was employed. In total, 82 nursing students taking psychiatric nursing participated in the study, with 39 in the experimental group and 43 in the control group. The experimental group participated in an escape room activity, while the control group engaged in a scenario-based group discussion for 50 minutes. The data were analyzed using the Mann-Whitney U test and the Wilcoxon signed-rank test with SPSS/WIN version 29. Results: No statistically significant differences were identified between the groups in terms of knowledge, proactivity in problem-solving, teamwork, and learning satisfaction. However, proactivity in problem-solving (Z=-3.47, p<.001) and teamwork (Z=-3.55, p<.001) were significantly increased for the experimental group in the post-test, while knowledge (Z=-2.40, p=.027), proactivity in problem-solving (Z=-3.96, p<.001), and teamwork (Z=-2.08, p=.037) were significantly increased in the control group when compared to the pretests. Conclusion: Both the escape room activity and the group discussion were effective in improving proactivity in problem solving and teamwork among nursing students and should therefore be incorporated into classes.